Recycling of subducted continental crust: geochemical evidence from syn-exhumation Triassic alkaline mafic rocks of the southern Liaodong Peninsula - Hu, Zhaoping; Zeng, Lingsen; Förster, Michael W.; Zhao, Linghao; Gao, Lie; Li, Huan; Yang, Yizeng; Li, Shuang-Qing (Lithos, 2021)
Syn-exhumation mafic magmatism during continental collision provides insights into the crust-mantle reaction during deep subduction and the nature of orogenic lithospheric mantle in collisional orogens. In this study, we present a comprehensive data set of zircon U-Pb ages and whole-rock major-trace elements as well as Sr-Nd-Pb isotopes of alkaline mafic rocks from the southern Liaodong Peninsula, eastern China. Zircon U-Pb analyses yield Late Triassic age of 213 ± 3 to 217 ± 3 Ma, younger than the Middle Triassic ultrahigh-pressure metamorphic rocks of the Dabie-Sulu orogen. Thus, the alkaline mafic rocks are products of syn-exhumation magmatism during continental collision of the South and North China blocks. The rocks show shoshonitic affinities with high K2O (3.78-5.23 wt%) and K2O/Na2O (0.71-1.22). They are characterized by arc-like trace-element patterns with enriched LILE, Pb, and LREE, and depleted HFSE. They exhibit enriched Sr-Nd isotopic compositions with high initial 87Sr/86Sr isotopic ratios of 0.7058-0.7061 and negative εNd(t) values of −13.0 to −15.1. These results suggest involvement of recycled continental crust in their mantle source. The mantle source likely formed by the metasomatic reaction of subducted continental crust-derived melts with the overlying subcontinental lithospheric mantle during the Triassic continental collision. Decompressional melting of this metasomatized mantle formed syn-exhumation mafic magmas during the transition from convergent to extensional tectonics in the Late Triassic. Accordingly, mafic rocks from the southern Liaodong Peninsula provide a geochemical record of the subduction and recycling of continental crust into the mantle and melt-mantle reaction induced metasomatism within the orogen.